The Effect of Ethynil Estradiol and Desogestrel on Proliferation and Apoptosis Hydatidiform Mole Trophoblast Cell - Irawan Sastradinata; Andrijono; Mohamad Farid Aziz; Wan Lelly H; Sri Hartini; Bambang Sutrisna (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: To explore the effect of ethynil estradiol and desogestrel on proliferation and apoptosis hydatidiform mole trophoblast cell. Methods: From April 2008 until March 2009, we collected 15 samples of hydatidiform mole tissue. Trophoblast cells was isolated and culture at RPMI 20% FBS medium. Only 7 samples (46%) shown good growth. Cell was identified using cytology and β HCG test. Trophoblast cells good quality than devided into three groups observation. First group get ethynil estradiol 10 nmol/mL, second group get desogestrel 100 nmol/mL, Third group get DMSO 1%. Cells incubated and observe at 24, 48, 72, 96 hours. Cell cycle, apoptosis and β HCG was evaluated at each time observation. Cell cycle evaluation using BD cycle test plus DNA reagent, apoptosis evaluation using FITC-Annexin V. Analyze using FACSCalibur flowcytometer. β HCG evaluation using Abbott AxSym total β-HCG reagent pack. Results: The group of cell that get ethynil estradiol in concentration 10 nmol/mL had cell proliferation index, amount cells and β HCG level higher than control after 72 hours observation. The group of cell that get desogestrel in concentration 100 nmol/mL have cell proliferation index, amount cells and β HCG level lower than control after 48 hours observation. There are no differences of apoptosis between the two group and control. Conclusion: Ethynil estradiol will increase proliferation of hydatidiform mole trophoblast cell, while desogestrel will decrease proliferation of hydatidiform mole trophoblast cell. There are no effect of ethynil estradiol and desogestrel on apoptosis of hydatidiform mole trophoblast cell.